Spatial Distribution, Behaviour, and Biological Aspect of Albacore (Thunnus alalunga) Caught in Eastern Indian Ocean - Fathur Rochman; Irwan Jatmiko; Bram Setyadji (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2017)
This study highlighted the occurrence of the Indonesian tuna longline fishery targeting albacore (Thunnus alalunga) caught in the Eastern Indian ocean. The data used in this study based on the Research Institute for Tuna Fisheries (RITF) observer program in Benoa. This paper presents the current information on biological aspect (size distribution and length-weight relationship) and fish behavior (swimming layer and feeding periodicity) of albacore. Total albacore samples of  3,152 were taken from scientific observer data from 2010-2013. The study area of albacore was between 0-33°S and 75-131°E. Albacore length  distributed from 70-196 cmFL (median=93 cmFL, mode=100 cmFL, mean=92.12 cmFL) and dominated at size of 95 cmFL. The highest percentage length of albacore was  >90 cm (L50) occured in the area between (30-35°S and 80-95°E) and (10-15°S and 120-125°E). The length weight relationship was determined to be W=0.0045 FL1.8211  (W in kg, FL in cm). The expected season to catch the ALB was from April to July with the peak season in June and July. The swimming layer of albacore based on minilogger data were distributed from at 118 to 341 m depth and mostly catch at depth of 156 m with temperature degree 18°C.  The feeding periodicity of albacore’s are start from 7:45am to 17:59 pm, mostly active at 10 am to 11 am. The majority of ALB caught by Indonesian longliner was mature condition and negative allometric growth. The ALB peak season was in June-July and the best time to catch was 10 am to 11 am at depth of 156 m. Keywords : albacore, feeding periodicity, swimming layer,  CPUE